Optimizing Electroactive Organisms: The Effect of Orthologous Proteins - Fonseca, Bruno M.; Silva, Luís; Trindade, Inês B.; Moe, Elin; Matias, Pedro M.; Louro, Ricardo O.; Paquete, Catarina M. (Frontiers in Energy Research, 2019)
Extracellular electron transfer pathways allow bacteria to transfer electrons from the cell metabolism to extracellular substrates, such as metal oxides in natural environments and electrodes in microbial electrochemical technologies (MET). Studies of electroactive microorganism and mainly of Shewanella oneidensis MR-1 have demonstrated that extracellular electron transfer pathways relies on several multiheme c-type cytochromes. The small tetraheme cytochrome c (STC) is highly conserved among Shewanella species and is one of the most abundant cytochromes in the periplasmic space. It transfers electrons from the cell metabolism delivered by the inner-membrane tetraheme cytochrome CymA, to the porin-cytochrome complex MtrCAB in the outer-membrane, to reduce solid electron acceptors outside the cell, or electrodes in the case of MET. In this work knock-out strains of STC of S. oneidensis MR-1, expressing STC from distinct Shewanella species were tested for their ability to perform extracellular electron transfer, allowing to explore the effect of protein mutations in living organisms. These studies, complemented by a biochemical evaluation of the electron transfer properties of the individual proteins, revealed a considerable plasticity in the molecular components involved in extracellular electron transfer. The results of this work are pioneering and of significant relevance for future rational design of cytochromes in order to enhance extracellular electron transfer and thus contribute to the practical implementation of MET.